1974
DOI: 10.1159/000224961
|View full text |Cite
|
Sign up to set email alerts
|

Phase I–II Evaluation of Weekly Mitomycin-C (NSC-26980) for Patients with Metastatic GI and Breast Malignancies

Abstract: The experience of Mitomycin-C given as a once weekly intraveneous injection for carcinoma of gastroenteric and breast origin with review of recent literature is given. Limited activity was seen in gastric and colorectal carcinoma. Similar to the experience of others, hematological toxicity (thrombocytopenia and/or leukopenia) was the dose-limiting toxicity encountered. Although the once weekly schedule was not directly compared with other reported schedules, it seems clear there was no reduction of significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1978
1978
1993
1993

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Although the lack of response in those cases reported by Hum et al [18] and Saba et al [19] has been related to the low drug dosage used (0.125 mg/kg/week), Creech et al [14] recently ob tained a 16% response rate in 90 patients treated with doses as low as 10 mg/m2 of MMC every 4 weeks. On the other hand, De Lena et al [7] observed only one partial response using dosages of MMC as high as 20 mg/m2 every 6 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the lack of response in those cases reported by Hum et al [18] and Saba et al [19] has been related to the low drug dosage used (0.125 mg/kg/week), Creech et al [14] recently ob tained a 16% response rate in 90 patients treated with doses as low as 10 mg/m2 of MMC every 4 weeks. On the other hand, De Lena et al [7] observed only one partial response using dosages of MMC as high as 20 mg/m2 every 6 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Mitomycin C (MMC) has been found to be active in a variety of tumors, and an objective response rate of nearly 35% has been reported in advanced breast cancer [2,18,22], Nevertheless, these early trials, using the drug on chronic schedules, have generated little enthusiasm because of unacceptable hematologic toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Eleven of the 26 (42%) had some objective evidence of response. A weekly schedule of administration was initiated by Hum ct al [5], who reported their experience with 54 eva luable patients. Because of progressive toxicity, the start ing dose (10 mg/nr/week) was decreased to 5 mg/m2/ week.…”
Section: Single-agent Trialsmentioning
confidence: 99%